Upaya Meningkatkan Hasil Belajar Servis atas Permainan Bolavoli Menggunakan Media Pembelajaran Alat Bantu pada Siswa Kelas X Smk Taruna Bakti Kertosono Tahun Ajaran 2022/2023 - Faqih, Achmad Zulva Ainun; Muharram, Nur Ahmad; Setiawan, Irwan (Jurnal Kridatama Sains dan Teknologi, 2022)
The purpose of this research is to improve the learning outcomes of serve on volleyball in class X students of SMK Taruna Bakti Kertosono Academic Year 2022/2023. This research is a Classroom Action Research (CAR). This research was conducted in two cycles and consisted of four stages in each cycle, namely planning, action, observation and reflection. The subjects in this Classroom Action Research were class X students of SMK Taruna Bakti Kertosono Academic Year 2022/2023 with a total of 28 students consisting of 19 male students and 9 female students. Sources of data in this study came from students, researchers and teachers who acted as collaborators. Data collection techniques using tests and observations. Data validity uses data triangulation techniques. This classroom action research is a percentage to see trends that occur in learning activities. the results of the analysis obtained a gradual increase from pre-cycle to cycle I and from cycle I to cycle II. This can be seen from the results of service learning for volleyball games for pre-cyclical students, it shows that out of 28 students cognitively, 8 students or 28.57% have completed, while 20 students or 71.42% have not completed and from the psychomotor aspect there are 7 students. or 25.00% complete. Then the results of learning to serve for volleyball games shown by students in the first cycle of the cognitive aspect showed an increase of 28.57% where there were 16 students or 57.14% included in the complete category while for the psychomotor aspects showed an increase of 35.71% where there were 17 students or 60.71% fall into the complete category. In cycle II the improvement of student learning outcomes is better. Cognitive aspects increased by 21.43% from the first cycle and 50.00% from the pre-cycle, while the psychomotor aspects increased by 25.00% from the first cycle and 60.71% from the pre-cycle. In cycle II the cognitive aspect had 22 students or 78.57% in the complete category, 6 students or 21.42% of students were in the incomplete category and for the psychomotor aspect there were 24 students or 85.71% in the complete category, 4 students or 14.28% of students are in the incomplete category. Based on the results of the study, it was concluded that the application of learning models using assistive devices can improve service learning outcomes for volleyball games in class X students of SMK Taruna Bakti Kertosono Academic Year 2022/2023. Keywords: top serve, volleyball, Classroom Action Research